Предмет: Алгебра,
автор: violettashevv
Упростите выражение (2a-3)(5a+1)-(3a-1)^2
Буду благодарна за ответ
Ответы
Автор ответа:
1
Вот и ответ))) Если перемотаешь фотографию вниз там появиться ответ
Приложения:
Автор ответа:
1
(2a-3)(5a+1)-(3a-1)²=10a²-13a-3-(9a²-6a+1)=10a²-13a-3-9a²+6a-1=
=a²-7a-4.
Похожие вопросы
Предмет: Алгебра,
автор: volkovanadia42
Предмет: Математика,
автор: Kira20065
Предмет: Геометрия,
автор: karinamhitaran717
Предмет: Алгебра,
автор: Руслан7718
Предмет: Литература,
автор: misterloloshka